Systematic review of current randomised control trials in chronic subdural haematoma and proposal for an international collaborative approach (2020)
Abstract Background Chronic subdural haematoma (CSDH) is a pathology that is frequently encountered by neurosurgeons. Nevertheless, there is a lack of guidelines based on solid evidence. There has been a recent and considerable increase in the interest on management and outcomes for CSDH. Therefore, we systematically reviewed all currently running randomised controlled trials (RCTs) in chronic subdural haematoma to understand the areas under investigation and plan future collaborative trials. Methods Clinical trials databases (Cochrane Controlled Register of Trials, WHO ICTRP and clinical trials.gov) were searched for trials relevant to chronic subdural haematoma. It was then established which trials were currently running and fulfilled robust research methodology for a RCT. Results There are 26 currently running RCTs in CSDH, with the most common topics covering application of steroids (7), surgical techniques (5) and tranexamic acid (5). Further to this, there are trials running on other pharmacological agents (4), middle meningeal artery (MMA) embolisation (2) and peri-operative management (3). Conclusions Pharmacological agents are a particular focus of CSDH management currently, and a wealth of studies on steroids will hopefully lead to more harmonised, evidence-based practice regarding this in the near future. Surgical techniques and new procedures such as MMA embolisation are also important focuses for improving patient outcomes. There is an on-going need for future RCTs and evidence-based guidelines in CSDH, particularly including low- and middle-income countries, and it is hoped that the establishment of the iCORIC (International COllaborative Research Initiative on Chronic Subdural Haematoma) will help address this.